Experimental Investigations on Microstructure and Mechanical Properties of L-Shaped Structure Fabricated by WAAM Process of NiTi SMA - Vatsal Vaghasia; Rakesh Chaudhari; Sakshum Khanna; Jash Modi; Jay Vora (Journal of Manufacturing and Materials Processing)
In the present study, an L-shaped multi-walled structure of NiTi shape memory alloy (SMA) was fabricated by using the wire arc additive manufacturing (WAAM) method on a titanium substrate. The present study aims to investigate the fabricated structure for microstructure, macrostructure, and mechanical properties. The 40 layers of L-shaped structure were successfully fabricated at optimized parameters of wire feed speed at 6 m/min, travel speed at 12 mm/s, and voltage at 20 V. The macrographs demonstrated the continuous bonding among the layers with complete fusion. The microstructure in the area between the two middle layers has exhibited a mixture of columnar grains (both coarse and fine), interspersed with dendritic colonies. The microstructure in the topmost layers has exhibited finer colonial structures in relatively greater numbers. The microhardness (MH) test has shown the average values of 283.2 ± 3.67 HV and 371.1 ± 5.81 HV at the bottom and topmost layers, respectively. A tensile test was conducted for specimens extracted from deposition and build directions, which showed consistent mechanical behavior. For the deposition direction, the average ultimate tensile strength (UTS) and elongation (EL) were obtained as 831 ± 22.91 MPa and 14.32 ± 0.55%, respectively, while the build direction has shown average UTS and EL values of 774 ± 6.56 MPa and 14.16 ± 0.21%, respectively. The elongation exceeding 10% in all samples suggests that the fabricated structure demonstrates properties comparable to those of wrought metal. Fractography of all tensile specimens has shown good ductility and toughness. Lastly, a differential scanning calorimetry test was carried out to assess the retention of shape memory effect for the fabricated structure. The authors believe that the findings of this work will be valuable for various industrial applications.